Chapter II: Graphic Analysis: Curves and Equations (Quarterly Journal of Economics, 1938)
Chapter II: Graphic Analysis: Curves and Equations Get access The Quarterly Journal of Economics, Volume 52, Issue Supplement, May 1938, Pages 27–51, https://doi.org/10.1093/qje/52.Supplement.27 Published: 01 May 1938